2020
DOI: 10.3390/brainsci10060336
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Profiles of Children with Autism Spectrum Disorder with and without Feeding Problems: A Comparative Study in Sicilian Subjects

Abstract: The aim of this study is to better understand the relationship between sensory and feeding problems in Autism Spectrum Disorder (ASD) by comparing sensory responsiveness of ASD children with (ASD-W) and without (ASD-WO) feeding problems. The feeding and sensory characteristics of 111 children with ASD (37 ASD-W and 74 ASD-WO) were assessed by using two questionnaires tapping on feeding problems and two on sensory problems. A comparative study was carried out with between-group as well as intra-group comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
3
17
0
1
Order By: Relevance
“…Padmanabhan and Schroff (2020) and Wang et al (2014) reported multi-modal correlations between sensory processing and mealtime behaviours, with the strongest associations observed for taste/smell sensitivities and stronger evidence reported in Wang et al (2014)'s autism sample compared to neurotypical peers. Finally, Panerai et al (2020) found that autistic children with feeding problems exhibited higher multi-modal sensory differences compared to those without, with the largest effect size (0.52) being for taste/smell sensitivities. Furthermore, this was the only study that differentiated between hyper-and hypo-sensitivity patterns and found significant differences between autistic children with feeding problems demonstrated greater impairments in hypersensitivities (Panerai et al, 2020).…”
Section: General Mealtime and Eating Behavioursmentioning
confidence: 90%
“…Padmanabhan and Schroff (2020) and Wang et al (2014) reported multi-modal correlations between sensory processing and mealtime behaviours, with the strongest associations observed for taste/smell sensitivities and stronger evidence reported in Wang et al (2014)'s autism sample compared to neurotypical peers. Finally, Panerai et al (2020) found that autistic children with feeding problems exhibited higher multi-modal sensory differences compared to those without, with the largest effect size (0.52) being for taste/smell sensitivities. Furthermore, this was the only study that differentiated between hyper-and hypo-sensitivity patterns and found significant differences between autistic children with feeding problems demonstrated greater impairments in hypersensitivities (Panerai et al, 2020).…”
Section: General Mealtime and Eating Behavioursmentioning
confidence: 90%
“…Embora a redução da saturação de O2 neste estudo pareça um fator negativo da intervenção de musicoterapia realizada, por outro lado, é preciso destacar que crianças com TEA possuem um padrão de comportamento mais sensível a elementos estressores do ambiente, que podem levar ao aumento da saturação de O2, em decorrência da hiperventilação proveniente de agitação psicomotora e aumento dos níveis de adrenalina (Panerai et al, 2020;Le Menn-Tripi et al, 2019).…”
Section: Discussionunclassified
“…In fact, pharmacological therapies commonly prescribed to individuals with ASD are frequently burdened by side effects, such as weight gain, dyslipidemia, diabetes, and metabolic syndrome. These adverse events are also frequent in children, given the sensory difficulties, food selectivity, and rigidity in eating behaviors, which can lead to an increased risk for weight gain and poor nutritional habits [ 68 , 69 , 70 , 71 ]. For this reason, the correct management of pharmacological treatment should try to prevent the onset of side effects, through reviewing and identifying the risk factors, monitoring metabolic markers, and promoting potential modifiers of the course of metabolic syndrome (i.e., lifestyle, polypharmacy) [ 72 ].…”
Section: Discussionmentioning
confidence: 99%